Comment on "I exist, therefore the world thinks: Whitehead, Latour and scientific aesthetics" - Bezerra, Julio (2023)
Commented article reference: PINHO, Thiago. Existo, logo o mundo pensa: Whitehead, Latour e a estética científica. Trans/Form/Ação: Revista de Filosofia da Unesp, v. 47, n. 3, e0240032, 2024. Acess: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14195https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14195